Why Exhibit? vol. 2 : on curating photography - (:unkn) unknown (Fw:Books, Amsterdam, Co-publisher: The Academy of Fine Arts, University of the Arts Helsinki, 2024)
Why Exhibit? vol. 2 combines articles and conversations on curatorial practices concerning photo-based images. Discussion centers on challenges curators and artists working with photography face today. How do they navigate its constantly changing appearance? How are issues of representation dealt with? How do they handle the weight of the history of the medium, which is often hidden in power structures and silenced narratives? And what kind of mediation is necessary while seeking new forms of authorship and interaction with audiences? This book primarily focuses on practical perspectives intertwining photography and curation. It offers insights into a wide range of experiences, reflections, and views from the perspective of curators, photographers, visual artists, writers, and researchers. These conversations are vital for curating photography in light of pressing issues surrounding the medium.
Introduction / Anna-Kaisa Rastenberger and Iris Sikking Curating Photography Blind Spots: Introduction to Photo Curation as Confrontation / Anna-Kaisa Rastenberger Directing the Body and Mind: Cinematic Narration in a Photography Exhibition / Iris Sikking Photography Is Not Enough! / Sergio Valenzuela Escobedo In conversation with Kateryna Radchenko (Phone Photography as a Protective Tool in Wartime Ukraine) In conversation with Yining He on Creating Cultural Exchange In conversation with Laura Toots (Curating by Using Manners of Friendship) In conversation with Thomas Kuijpers on the Volume of Images With Whom Are We Curating? Whatever We Curate, We Curate Ecology: Multispecies Relationships and Photography in Curatorial Praxis / Eszter Erdosi Curating in a Changing Climate: Situated, Mediated, Dependent / Taru Elfving Homeless Photographs: Approaches in Photographing Participation and Participating in Pphotographing / Kaija Kaitavuori In conversation with Tanvi Misra on Collective Gathering In conversation with Salvatore Vitale on a Technologically Mediated Reality Who Is Telling the Story? Reinterpreting the Script: Activating Archives, Managing Dissonance / Sunil Shah In conversation with Anastasia Mityukova (Project Iceworm: A Fragile Excavation through Photography) In conversation with Poulomi Basu on a Collision of Truths In conversation with Anna Ehrenstein on Power Structures In conversation with Giya Makondo-Wills on Images without Caption Who Are We Speaking with? com/exhibition-enter, or: Photographic Shows Gone 🌐 / Daria Tuminas The Appropriateness of Images: Exhibiting Image Appropriations after Deepfakes / Lia Carreira In conversation with Uwa Iduozee (To Be Apolitical Is a Privilege) In conversation with NayanTara Gurung Kakshapati on Shifting the Focus In conversation with Tina Farifteh on Speaking Out against Power Contributors and Artists.
Keywords: Photography, Artistic--21st century; Curatorship; valokuvataide; valokuvanäyttelyt; kuratointi; näyttelytoiminta; photographic art; photography exhibitions; curation (collections); exhibition activity